EFFLEURAGE MASSAGE WITH VIRGIN COCONUT OIL (VCO) TO PREVENT DECUBITUS ULCERS IN IMMOBILIZED PATIENTS: A CASE STUDY - Nuzulullail, Agung Subakti; Pranata, Satriya; Armiyati, Yunie; Chanif, Chanif (Journal of Vocational Nursing, 2023)
Introduction: Some of the problems that arise due to incomplete mobilization, the most common are decubitus ulcers. Massage effleurage (ME) is used as a non-pharmacological intervention that can be given to patients who are immobilized, aiming to keep the skin moist. In the final scientific work of this nurse. The author purpose was to determine the effect of giving ME with Virgin Coconut Oil (VCO) in patients at risk of pressure sores. Methods: This case study uses a descriptive method with a nursing care approach. The case study will be carried out in December 2022, in the Rajawali Room 3A RSUP Dr. Kariadi Semarang on 2 respondents. The respondent's inclusion criteria were immobilized patients for more than 2 weeks with a risk of developing pressure sores. Giving massage with VCO is done 2 times a day for 5 days, on areas of pressure such as the sacrum, scapula, and heels with a total duration of 45 minutes. The instrument used in this case study is the Braden Scale to measure the risk of pressure sores, the fewer scores obtained, the higher the risk of decubitus. Results: After 5 days of intervention, first responders experienced a decrease from a score of 8 (very high risk) to a score of 13 ( high risk), then for the second respondent from a total score of 7 (very high risk) to a score of 9 (very high risk), the higher the score obtained, the lower the risk of decubitus. Conclusions: Administering ME with VCO has a positive effect on reducing decubitus risk scores in immobilized patients.